Négocier la climatisation de la strate glaciaire. Le cas du projet d’aménagement du troisième tronçon du téléphérique de La Grave - Marie Poulain; Pierre-Olivier Garcia (Revue de Géographie Alpine)
Located in La Grave, French Hautes-Alpes, the Girose glacier is a recreational and tourist site. In the winter season, it is a freeride skiing area, accessible by cable car since 1978 and completed by ski lifts since 1989. During summer, the Girose is a glacier tourism site, offering activities on and around the glacier. However, since 2020, this site become embroiled in a territorial conflict over the planned extension of a third section of the cable car, with could take visitors beyond the glacier to an altitude of 3,600m. This ongoing conflict in 2023 has caused significant tensions in La Grave. The project highlights a challenge in initiating a public and political discussion on the spatiotemporal trajectory of the territory.This article is based on a qualitative study carried out at La Grave between January 2021 and July 2022. It analyses the Girose Glacier as a glacial stratum in the light of the emerging field of political geology. The regional development’s project has been structured around the cable car for over thirty years. This article explores the implications of this structure as we have observed a process of unintentional climatization of the territory at La Grave, due to geomorphological changes linked to the consequences of climate change on the glacier, territorial conflict, and state institutions. Although the territory seems to be closely tied to the cable car and the glacier, the conflict provides the opportunity to explore alternative approaches to rearranging in response to an uncontrollable and disaggregating glacier stratum. We describe four ways of rearranging the situation as expressed by the respondents: climate denial, anticipating a mountain as a resource without the Girose, reopening the territorial project, and the local truth of the regional developer. In conclusion, negotiating with terrestrial strata seems to be a transition strategy regarding terrestrial processes that always exceed territorial projects.